KONSEP KEPEMIMPINAN PERSPEKTIF TASAWUF POSITIF MODERN - Ahmad Buchori Muslim (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2019)
Sufism as the core of Islamic teachings emerged by providing solutions and therapies for human problems by bringing closer to Allah the Creator. However, Sufism has been perceived as an inner practice that detaches itself from the world. However, lately, there is an understanding of Sufism which does not make its practitioners withdraw from the environment and instead requires its practitioners to go down to the community and contribute to solving problems faced by their communities. Sufism is known as "Positive Sufism" or neo-Sufism. Positive Sufism is a turning point of conservative Sufism. If conservative Sufism suggests that Sufism surges, then positive Sufism gives the impression that Sufism must be grounded. It must appear in all social life, and also contribute to solving world problems. This includes issues regarding leadership. The study method used is qualitative, the method of presenting the data is descriptive analysis, and it is designed with a library approach that explores some of the literature relating to the discussion of leadership concepts of modern positive Sufism perspectives. Therefore reviewing the concept of leadership and the criteria of a leader in the realm of Sufism is an alternative that can be done. So that it is expected to give an alternative picture like a leader who wants to run the wheel of his leadership based on Sufi souls, a Sufism expert